ZnO -Graphene Nanocomposites: Synthesis, Characterization, And Applications - Bhanu Priya; Sunita Bishnoi; Rupali Shrivastava (Revista Electronica de Veterinaria, 2024)
ZnO-graphene nanocomposites present a versatile and promising platform with numerous applications across various fields, including human and veterinary medicine. Their unique combination of properties, such as antibacterial activity, biocompatibility, electrical conductivity, and mechanical strength, makes them valuable in addressing a wide range of challenges and needs in healthcare and biomedicine. In human medicine, ZnO-graphene nanocomposites have shown potential in areas such as drug delivery, wound healing, biosensing, cancer therapy, and biomedical imaging. They offer innovative solutions for improving treatment outcomes, enhancing diagnostic capabilities, and advancing medical device technologies. Continued research and development in ZnO-graphene nanocomposites hold promise for further expanding their applications and optimizing their performance in both human and veterinary healthcare settings. As advancements continue, these nanocomposites are poised to play a significant role in advancing medical and veterinary treatments, improving patient outcomes, and contributing to overall health and well-being. The synthesis, characterisation, uses, and prospects for ZnO–Graphene nanocomposites in the future offer a constantly evolving field of scientific inquiry and technological advancement. This abstract highlights important elements that define the storey of these cutting-edge materials, thereby capturing the spirit of this complex journey. The production of ZnO–Graphene nanocomposites is characterised by an ongoing pursuit of accuracy and consistency. To accomplish successful integration, researchers have used a variety of synthetic processes, such as sol-gel methods and chemical vapour deposition. A primary goal is to optimise these techniques in order to guarantee consistency in the properties of the nanocomposites and improve scalability. The synthesis procedure is the cornerstone upon which ZnO–Graphene nanocomposites’ special qualities and capabilities are constructed. When it comes to deciphering the complex structural features of ZnO–Graphene nanocomposites, characterization procedures are essential. Together, Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD) provide a thorough understanding of the composition, shape, and internal structure of the nanocomposites. Researchers find these techniques to be quite useful since they offer valuable insights that help fine-tune the properties of nanocomposite materials for certain applications. ZnO-Graphene nanocomposites have a wide range of applications, which demonstrate their adaptability and versatility. These nanocomposites have remarkable photocatalytic qualities that aid in the breakdown of contaminants in the air and water during environmental restoration. The special combination of graphene’s conductivity and ZnO’s semiconducting qualities makes for extremely sensitive and selective sensors in sensing technologies. The energy storage capacity of the nanocomposites is greatly increased, improving the efficiency of batteries and supercapacitors. They boost solar cell performance in photovoltaics, and their biocompatibility is utilised in biomedical applications for imaging and medication delivery. ZnO-Graphene nanocomposites have an exciting trajectory of innovation ahead of them. Scientists are ready to further refine synthesis techniques such that they are repeatable and scalable. At the forefront of research are improved nanocomposite qualities designed for particular uses. The next stage of these materials’ evolution will be defined by innovative uses, integration with cutting-edge technologies, and a dedication to sustainable methods.